Yahoo Web Search

  1. Ads
    related to: ss
  1. T( S ) = {T( s ) | s is in S }. Clearly T( S ) ... under scalar multiplication and vector addition. Let x,y be in T( S ) and k be a scalar. Then x = T( s ) and y = T(t) for some s ,t...

    1 Answers · Science & Mathematics · 15/07/2009

  2. s : or : s is an uncertain/confused face. The : is the eyes and the s is the squiggly, unsure mouth.

    3 Answers · Education & Reference · 16/09/2011

  3. -11=9 s +7 -11-7=9s -18=9s s = -18/9 s = -2

    7 Answers · Education & Reference · 12/11/2010

  4. s ^3-3s^2+3s-1 use grouping s ^3-1-3s^2+3s ( s ^3-1)-3s( s -1) now you can factor s ^3-1 more... s -1)[ s ^2+ s +1-3s] ( s -1)[ s ^2-2s+1] you can factor the inside ( s -1)[( s -1)( s -1)] ( s -1)^3 is in the denominator. Partial...

    2 Answers · Science & Mathematics · 16/03/2012

  5. ...exponential term folds into that, changing it to e^( s (t-π/6). So you can drop that, and just replace t with t... answer: Inverse Laplace transform of Y( s ) = s Exp[-π s /6]/(( s +1)( s ^2+9))

    1 Answers · Science & Mathematics · 01/11/2016

  6. S ... sulfur has an electron config of 3P4, that s 2 unpaired...the three P-orbitals Px(ii) Py (i ) Pz (i ) S + has lost one out of the pair , & so has 3 unpaired: in the...

    1 Answers · Science & Mathematics · 05/09/2008

  7. Given sqrt(x+ s ) = (1/x) + (1/ s ) derivative with respect to x Modifying the expression a little...1/ s ) = ( s + x)/sx Taking square of both sides of equation x + s = ( s + x)^2/ s ^2x^2 1 = ( s + x)/ s ^2x^2 s ^2x^2 = s + x Taking derivative...

    3 Answers · Science & Mathematics · 07/11/2013

  8. s - a =12, s - b = 8, s - c = 6 where s is the semiperimeter (a + b + c)/2 Add the given equations s - a + s - b + s - c = 26 3s - (a + b + c) = 3s - 2s = s = 26. Now use...

    3 Answers · Science & Mathematics · 06/05/2014

  9. s = a+2(x+1) s -a = 2(x+1) ( s -a)/2 = x+1

    1 Answers · Science & Mathematics · 25/09/2007

  10. s ^3 + 12s^2 + 36s First take S common from all terms: s ( s ^2 + 12s + 36) Now Factorize: s ( s ^2 + 6s + 6s + 36) s [ s ( s +6) + s ( s +6)] s ( s +6) ( s +6) s ( s +6)^2 Here you go....

    3 Answers · Education & Reference · 05/03/2010

  1. Ads
    related to: ss
  1. Try asking your question on Yahoo Answers